2022
DOI: 10.3389/fphar.2022.1056687
|View full text |Cite
|
Sign up to set email alerts
|

Calycosin induces autophagy and apoptosis via Sestrin2/AMPK/mTOR in human papillary thyroid cancer cells

Abstract: Calycosin, one of small molecules derived from astragalus, has anti-tumor effects in various tumors. However, the effects of calycosin on papillary thyroid cancer (PTC) remain unclear. This study aimed to explore the anti-tumor ability of calycosin on human PTC and its potential mechanisms. The B-CPAP cells were treated with calycosin, then cell proliferation, apoptosis and invasiveness were measured by CCK8 assay, flow cytometry, wound healing and transwell invasion assay, respectively. The cells were also pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…Malignant cell formation in the tissue of the thyroid gland results in the most common endocrine tumor, that is, thyroid cancer. Calycosin has an inverse effect on thyroid cancer, for example, anti‐inflammatory, antioxidant, and anti‐tumor 66 . Human papillary thyroid cancer cells (B‐CPAP) and human normal thyroid cells (Nthy‐ori 3‐1) were treated with calycosin (0–100 μM), and the result demonstrated that calycosin suppresses the proliferation of cancer cells (B‐CPAP) 66 .…”
Section: Evidence Of Anti‐cancer Perspectives Regarding Calycosinmentioning
confidence: 99%
See 3 more Smart Citations
“…Malignant cell formation in the tissue of the thyroid gland results in the most common endocrine tumor, that is, thyroid cancer. Calycosin has an inverse effect on thyroid cancer, for example, anti‐inflammatory, antioxidant, and anti‐tumor 66 . Human papillary thyroid cancer cells (B‐CPAP) and human normal thyroid cells (Nthy‐ori 3‐1) were treated with calycosin (0–100 μM), and the result demonstrated that calycosin suppresses the proliferation of cancer cells (B‐CPAP) 66 .…”
Section: Evidence Of Anti‐cancer Perspectives Regarding Calycosinmentioning
confidence: 99%
“…66 The general pharmacological effects on human papillary thyroid cancer cells that are related to the activation of Sestrin2 (SESN2), upregulated p-AMPK (phosphorylated AMPK), and inhibits p-mTOR (phosphorylated mTOR) and p-p70S6Kinase (ribosomal protein S6 kinase). 66 Overall, calycosin induced anti-tumor, antiinflammatory, and antioxidant function and decreased cancer cell proliferation while regulating many pathways in thyroid cancer therapy.…”
Section: Thyroid Cancer (Tc)mentioning
confidence: 99%
See 2 more Smart Citations
“…[3,4] Additionally, it has been shown to offer protective effects on the heart, blood vessels, nerves, liver, kidney and against cancer. [5][6][7][8][9] Notably, several studies have highlighted the potential of CA as an anti-metastatic agent in various tumors, promoting apoptosis in cancer cells while exhibiting low toxicity to normal cells. [10] Despite these promising findings, the specific mechanism of action and its impact on different cancers remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%